Extracellular vesicles - mediating and delivering cardioprotection in acute myocardial infarction and heart failure - Prakash, Aishwarya (Cond Med, 2020)
New treatments are urgently needed to reduce myocardial infarct size and prevent adverse post-infarct left ventricular remodeling, in order to preserve cardiac function, and prevent the onset of heart failure in patients presenting with acute myocardial infarction (AMI). In this regard, extracellular vesicles (EVs) have emerged as key mediators of cardioprotection. Endogenously produced EVs are known to play crucial roles in maintaining normal cardiac homeostasis and function, by acting as mediators of intercellular communication between different types of cardiac cells. Endogenous EVs have also been shown to contribute to innate cardioprotective strategies such as remote ischemic conditioning. In terms of EV-based therapeutics, stem cell-derived EVs have been shown to confer cardioprotection in a large number of small and large animal AMI models, and have the therapeutic potential to be applied in the clinical setting for the benefit of AMI patients, although several challenges need to be overcome. Finally, EVs may be used as vehicles to deliver therapeutics to the infarcted heart, providing a potential synergist approach to cardioprotection. In this review article, we highlight the various roles that EVs play as mediators and deliverers of cardioprotection, and discuss their therapeutic potential for improving clinical outcomes following AMI.